Performance Analysis Of Electrical System Postgraduate University Of Lancang Kuning - Abrar Tanjung,; Zulfahri, (Human Sustainability Procedia, 2021)
The use of electrical energy generally shows an increase, because electricity is a very beneficial form of energy and helps humans in carrying out their lives. The need for electrical energy comes from generating electrical energy to the user, required network systems and distribution substations. The addition of the construction of the new Postgraduate Program Building is a factor due to the increase in the number of students who will study and study at Lancang Kuning University. Research Objectives to Analyze and determine the current load on the three phases of the electrical system, Calculate power consumption, Calculate power losses in the electrical system, Evaluating the Grounding System in the Unilak Postgraduate Program Building. Based on the calculation results obtained an average current size at a voltage of 3 phase 380 volts of 23.3 amperes, a large power capacity of 98 kW, a voltage drop of 14.4 volts, a large power loss of 328.45 watts and a large earth resistance value of 22.15 ohms. Whereas the measurement of earth resisting at the wire point is 66 ohms and at the neutral point of the measurement of 52 ohms, it means that the value of earth resistors in the Unilak postgraduate building exceeds the calculated value in the analysis of the discussion of earth resistance by 22.15 ohms.